Emulsions stabilized by cellulose-based nanoparticles for curcumin encapsulations: In vitro antioxidant properties - Zhang, Jian; Zhang, Huien; Liu, Liping; Chen, Zhongfa (Frontiers in Nutrition, 2022)
To improve the dispersity and antioxidant properties of curcumin, the curcumin emulsions covered with cellulose particle (CP) with different structures were successfully prepared, and the structural characteristics, stability and antioxidant properties of emulsions were investigated. The results showed that the CP obtained with increasing the hydrolysis time had smaller particle size, better water dispersion and interfacial adsorption capacity. The encapsulation efficiency of curcumin in emulsion stabilized by cellulose particle hydrolyzed for 10 h can reach about 80%. After 9 days, all emulsions showed good stability and no obvious creamed layer was observed. Compared to cellulose particle hydrolyzed for 2 h (CP2), emulsions stabilized by cellulose particle hydrolyzed for 6 h (CP6) and 10 h (CP10) exhibited better stability and free fatty acid (FFA) release. Meanwhile, DPPH scavenging activity of curcumin emulsion stabilized by CP significantly increased with increasing the hydrolysis time, and was much higher than that of pure emulsion and curcumin/water due to higher the solubility (1455 times compared with curcumin/water solution) of curcumin, these results could provide useful data for the stability and encapsulation of curcumin.